Incident Gout: Risk of Death and Cause-Specific Mortality in Western Sweden: A Prospective, Controlled Inception Cohort Study - Dehlin, Mats; Sandström, Tatiana Zverkova; Jacobsson, Lennart TH (Frontiers in Medicine, 2022)
Background Excess mortality in gout has been attributed to cardiovascular diseases (CVD). Considering the decline in CVD mortality in the general population, we wanted to evaluate overall mortality in gout and cause-specific contributions to mortality beyond CVD and temporal trends. Methods All incident cases of gout between 2006 and 2015 in western Sweden and 5 population controls per case matched for age, sex, and county were identified. Comorbidities were identified for 5 years preceding the index date. Follow-up ended at death, migration, or end of study on December 2017. Effect of gout on death risk was calculated using COX regression on the whole population and stratified by sex, adjusted for demographics, and comorbidities. Death incidence rates were compared between the two time periods, 2006–2010 and 2011–2015. Results We identified 22,055 cases of incident gout and 98,946 controls, median age (Q1, Q3) 69–68 (57, 79/56, 78) years and 67.6–66.5% males. Except for dementia, all comorbidities were significantly more common at baseline among gout cases. Overall, the risk for death in incident gout was neither increased overall nor in men, but women had a 10% elevated risk. In adjusted models for cause-specific mortality, death from CVD, renal disease, and digestive system diseases were significantly increased in the total gout population while death from dementia, cancer, and lung diseases were significantly decreased. There were no significant differences in overall incident death rate ratios between cases and controls in the two time periods examined. Conclusions An increased risk for CVD, renal disease, and diseases of the digestive system in patients with gout highlights the importance of addressing CVD risk factors in gout management. Gout was associated with reduced mortality from dementia, which may have implications on urate lowering therapy and possible effects on dementia risk.